Utility of Positive Suction Drain Tip Culture in Early Detection of Infection After Total Knee Replacement - Ammar Hafeez , Hamza Fareed , Nadia Atiq, Inamullah Shah, Ammar Hafeez , Hamza Fareed , Nadia Atiq, Inamullah Shah (Journal of Rawalpindi Medical College, 2019)
Introduction: To compare the frequency of wound infection in positive and negative drain tip culture in patients after primary total knee replacement. Methods: In this descriptive study patients undergoing primary total knee replacement for osteoarthritis were included. Early postoperative wound infection was defined as patient developing redness, pain, heat or swelling at surgical site; or drainage of pus within 7 postoperative days. Positive culture was considered as bacterial growth within 48 hours after suction drain tip was cultured on media. Negative culture was defined as no bacterial growth in 48 hours after placing the suction drain tip on culture media. Closed suction drain tips were sent for culture and sensitivity on 3rd postoperative day. Patients were followed for 7 days for any signs of infection. Effect modification was catered to by stratification for malnutrition defined as serum albumin less than 3.5g/dl; and obesity that was considered when BMI was equal to or more than 30kg/m2. Results: The mean age of patients was 57.28±7.37 years. Positive suction drain was found in 9.17% , while 6.67% had infection among all cases. Among 8 cases with infection there were 6(75%) who were positive on suction drain tip and among 112 non- infected cases there were 5(4.5%) who had positive suction drain tip. There was significant association between infection and suction drain tip positivity, p- value being < 0.001. Conclusion: Suction drain tip culture analysis can predict infection after primary total knee replacement.